Clinical characteristics and associated factors of insomnia among COPD outpatients at Bach Mai Hospital 2024 - 2025 - Ha, Le Thi Thu; Phuong, Do Hoai; Huyen, Nguyen Khanh (Tạp chí Nghiên cứu Y học, 2026)
Sleep disorders, particularly insomnia, are common in patients with Chronic Obstructive Pulmonary Disease (COPD) and significantly impact their quality of life. This study aimed to identify independent factors of insomnia in COPD patients. We conducted a cross-sectional study of 118 COPD outpatients at the Outpatient Department of Bach Mai Hospital. Insomnia was diagnosed using DSM-5 criteria, and multivariable modified Poisson regression was applied to estimate adjusted prevalence ratios (aPR). The prevalence of insomnia in this cohort was 44.1% (52/118). Multivariable analysis revealed that active respiratory symptoms, particularly current cough (aPR = 3.01; 95% CI: 1.57–5.77; p = 0.001) and dyspnea (aPR = 2.73; 95% CI: 1.78–4.18; p < 0.001). In contrast, the use of SABA (aPR = 0.54; 95% CI: 0.33–0.89; p = 0.015) and SAMA (aPR = 0.50; 95% CI: 0.28–0.89; p = 0.018) were associated with a reduced prevalence of insomnia. These findings suggest that current respiratory symptom burden is a major correlation of insomnia in COPD outpatients, while short-acting bronchodilator use may be associated with a lower prevalence of sleep disturbance.